Individual Rights versus Common Security? Christian Moral Reasoning about Torture - Biggar, Nigel (Studies in Christian ethics, 2014)
Should a Christian ethic endorse an individual’s right against torture? If so, how should its reasoning take into account considerations of common security? To answer these questions, this article first compares the early Christian ‘just war’ tradition’s pre-liberal reasoning about the ethics of harming with that of the liberal philosopher, David Rodin. It then deploys the fruits of this comparison—especially the contingency of a right against harm (partly upon social obligation), and the distinction between natural moral rights and positive legal ones—in an examination of what makes torture wrong and when. Dissenting from the views of Jeremy Waldron and Jean Porter, the article concludes that a positive legal right against torture and aggressive interrogation should be granted—even though morally right cases of the latter might occur.